THE DIFFERENCES OF PATIENT’S FAMILIES PERCEPTIONS WITH BPJS INSURANCE AND GENERAL ABOUT RESPONSE TIME NURSE’S BASED ON TRIAGE IN THE EMERGENCY ROOM - yeny martasari; Windu Santoso; Ana Zakiyah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Many families of BPJS or general patients assume that the nurse's response time is slow. The purpose of this study was to determine differences in family perceptions of BPJS and general patients about nurse response time based on triage in emergency room. The method in this study is quantitative descriptive with a comparative approach. The design used was cross-sectional with taking consecutive sampling techniques. The variables studied were differences in family perceptions of BPJS patients and the general about the response time of nurses based on triage in the emergency room. The results showed that the majority of patients including BPJS participants had a negative perception of 27 respondents (67.5%). And in General patients, most respondents had a positive perception of 17 respondents (42.5%). The results of the T-test obtained data p = 0.649> a = 0.05, H1 was rejected and H0 was accepted, meaning that there was no difference in family perceptions of BPJS patients and General about the response time of nurses based on triage in the emergency room. this is because the results of observations about the response time of the nurse show that the new patient is treated with the right time <5 minutes more than the slow one. This is because in the results of the questionnaire researchers have spread out, the results are more dominant with a mean value of 21.90 on the experience indicator.